GERAKAN PEMIKIRAN DAN PERAN TIGA ULAMA NU (K.H. HASYIM ASY’ARI, K.H.R. ASNAWI KUDUS, K. H. WAHHAB HASBULLAH) DALAM MENEGAKKAN AHL Al-SUNNAH WAL-JAMA’AH ANNAHDLIYAH DI JAWA TAHUN 1926 – 1971 - Solikhin, Mat (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2016)
AbstractThe role of the ulama founder of Nahdlatul Ulama with the historical development of NU is closely, like currency side. The pattern of the development of the mind with the organization cannot be removed from the thinking of the founding. K.H. Hasyim Ash'ari, K.H. Abdul Wahhab Hasbullah and K.H.R. Asnawi Kudus is three great figures that have a very important role in upholding the teachings and values of Ahl al-Sunnah wa al-Jama’ah in Java through both pesantren, ideas and the books written by them. This research aims to know the role of the leaders of the third phase of the development of Ahl al-Sunnah wa al-Jama’ah in Java and movements done by the three prominent figures in upholding the values of Ahl al Sunnah wa al- Jama’ah.Ahl al-Sunnah wa al-Jama’ah what is meant here is in the context of the NU s, where Ahl al- Sunnah wa al-Jama’ah be owned claims NU. Since it was established in 1926. The existence of the Hijaz Committee initiated by the K.H. Abdul Wahhab Hasbullah does not remove from several factors, one factor among others: international factors, religious ideologies and nationalities. With the formation of the Committee of the Hijaz was born Jam’iyah Nahdlatul Ulama as container and vehicle to preserve the values of Ahl al-Sunnah Wa al-Jama’ah al-Nahdliyah. The values of the Ahl al-Sunnah wa al-Jama’ah spread through boarding schools and books of the yellow and the results of the third ideas community.